2019
DOI: 10.1111/os.12562
|View full text |Cite
|
Sign up to set email alerts
|

One‐stage Debridement via Oblique Lateral Interbody Fusion Corridor Combined with Posterior Pedicle Screw Fixation in Treating Spontaneous Lumbar Infectious Spondylodiscitis: A Case Series

Abstract: ObjectiveSurgery is indicated when antibiotic treatment fails in pyogenic spondylodiscitis, which is caused by pathogens such as the Staphylococcus species. The aim of the present study was to investigate the efficacy and safety of the oblique lateral interbody fusion (OLIF) corridor approach combined with posterior pedicle screw fixation for treating pyogenic spondylodiscitis.MethodsThis was a retrospective case series study. A total of 11 patients with an average age of 60.7 years (range, 40–70 years; 10 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…The main purposes of surgery for lumbar spondylodiscitis include curing the infection and releasing the symptoms 22 . A previous study reported the efficiency and safety of the OLIF corridor approach in treating lumbar pyogenic spondylodiscitis 19 . Similarly, in this study, Mis-OLIF can relieve the symptoms of patients with lumbar spondylodiscitis, improve the diagnostic efficiency and treatment, and achieve good bony fusion.…”
Section: Clinical Effectiveness Of Mis-olifmentioning
confidence: 99%
See 1 more Smart Citation
“…The main purposes of surgery for lumbar spondylodiscitis include curing the infection and releasing the symptoms 22 . A previous study reported the efficiency and safety of the OLIF corridor approach in treating lumbar pyogenic spondylodiscitis 19 . Similarly, in this study, Mis-OLIF can relieve the symptoms of patients with lumbar spondylodiscitis, improve the diagnostic efficiency and treatment, and achieve good bony fusion.…”
Section: Clinical Effectiveness Of Mis-olifmentioning
confidence: 99%
“…Considering the advantages of OLIF, Mis-OLIF strategy may become an effective surgical approach to treat lumber spondylodiscitis. It has been reported that OLIF combined with posterior internal fixation is effective and safe for single-level spondylodiscitis after ineffective conservative treatment 19 . However, the internal fixation may not be necessary for patients with single-level lumbar spondylodiscitis without spinal deformity or epidural abscess.…”
Section: Introductionmentioning
confidence: 99%
“…Posterior lumbar interbody fusion, the classic surgical procedure to treat lumbar degenerative diseases and thoracolumbar fracture, has been developed for more than 70 years since the initial description in 1944 by Briggs and Milligan [1]. A large number of clinical studies have indicated that posterior-approach fusion and xation can effectively restore sagittal alignment, achieve immediate postoperative stability, and facilitate fusion rates [2][3][4]. However, consensus holds that the stiffness of the instrument relates directly to increased stress on the adjacent disc and facet joints, which could trigger segmental hypermobility and accelerate adjacent segment degeneration (ASD) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Posterior lumbar interbody fusion, the classic surgical procedure to treat lumbar degenerative diseases and thoracolumbar fracture, has been developed for more than 70 years since the initial description in 1944 by Briggs and Milligan [1]. A large number of clinical studies have indicated that posterior-approach fusion and fixation can effectively restore sagittal alignment, achieve immediate postoperative stability, and facilitate fusion rates [2][3][4]. However, consensus holds that the stiffness of the instrument relates directly to increased stress on the adjacent disc and facet joints, which could trigger segmental hypermobility and accelerate adjacent segment degeneration (ASD) [5,6].…”
Section: Introductionmentioning
confidence: 99%